Parents' Weekend. Photo 007 - Leonard, Spencer (Tufts Archival Research Center, 2008)
Parents' Weekend. Enjoy a leisurely guided tour of Civil War markers on the Medford/Somerville campus, highlighting Tufts' connection to this period in American history. Led by Cathy Stanton, lecturer in anthropology. Meet at the foot of Memorial Steps, College Avenue, 10 a.m.